用于航行器的优化的抗扭箱 (2018)
本发明公开种具有复合材料的抗扭箱（13）的航行器升力面，包括上蒙皮（21）、下蒙皮（23）、前翼梁（18）、后翼梁（20）、个或多个中间翼梁（19、19'）和布置在后翼梁（20）及其相邻的中间翼梁（19'）之间和/或前翼梁（18）和相邻的中间翼梁（19）之间的用于改善其结构特性的多个横翼肋（25、25'、...）。本发明还提供所述抗扭箱的制造方法。 The invention provides an aircraft lifting surface with a torsion box (13) of a composite material comprising an upper skin (21), a lower skin (23), a front spar (18), a rear spar (20), one or more intermediate spars (19, 19') and a plurality of transverse ribs (25, 25', ...) arranged between the rear spar (20) and its adjacent intermediate spar (19') and/or between the front spar (18) and the adjacent intermediate spar (19) for improving its structural behavior. The invention also provides a manufacturing method of said torsion box.